12.6k views
2 votes
Use implicit differentiation to justify both horizontal asymptotes for the curve

Use implicit differentiation to justify both horizontal asymptotes for the curve-example-1

1 Answer

2 votes

Given the equation of the curve:


y^2=x^3+3x^2...(1)

Using implicit differentiation:


\begin{gathered} 2y\cdot(dy)/(dx)=3x^2+6x \\ \\ (dy)/(dx)=(3x^2+6x)/(2y) \end{gathered}

For the points with the slope equal to 0, we have:


(dy)/(dx)=0

Using the expression above:


\begin{gathered} (3x^2+6x)/(2y)=0 \\ \\ (3x(x+2))/(2y)=0 \end{gathered}

The apparent solutions are x = 0 and x = -2, but if x = 0, then y = 0 (using equation (1)), so we have an indetermination of 0/0. Then, the only solution is x = -2. Using this solution on (1):


\begin{gathered} y^2=(-2)^3+3(-2)^2=-8+12=4 \\ \\ \Rightarrow y=2\text{ or }y=-2 \end{gathered}

And this result is consistent with the graph.

User Pugnator
by
5.0k points